2019
DOI: 10.1038/s41598-019-44470-2
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting methane emissions from upstream and downstream rivers and their associated subtropical reservoir in eastern China

Abstract: Subtropical reservoirs are an important source of atmospheric methane (CH 4 ). This study investigated the spatiotemporal variability of bubble and diffusive CH 4 emissions from a subtropical reservoir, including its upstream and downstream rivers, in eastern China. There was no obvious seasonal variation in CH 4 emissions from the main reservoir, which increased slightly from the first half year to the next half year. In the upstream river, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…In El Gergal both CO 2 and CH 4 emissions showed marked differences between riverine and lacustrine zones, highlighting the importance of including riverine areas to achieve accurate reservoir CO 2 and CH 4 emission assessments (Beaulieu et al, 2014;Yang, 2019), especially in heterogeneous ecosystems such as reservoirs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In El Gergal both CO 2 and CH 4 emissions showed marked differences between riverine and lacustrine zones, highlighting the importance of including riverine areas to achieve accurate reservoir CO 2 and CH 4 emission assessments (Beaulieu et al, 2014;Yang, 2019), especially in heterogeneous ecosystems such as reservoirs.…”
Section: Discussionmentioning
confidence: 99%
“…Ebullitive and diffusive fluxes were respectively 40 and 6 times greater in the riverine zone than those measured in the lacustrine. Shallow riverine areas have been previously identified as CH 4 emission hot spots in lakes and reservoirs (Bastviken et al, 2002;Beaulieu et al, 2014;Paraníba et al 2018;Yang, 2019), where CH 4 production is enhanced by deposition of fluvial organic matter, and a large fraction of sedimentary CH 4 is directly evading to the atmosphere through bubbling. The ebullitive CH 4 emissions measured in the shallow riverine zone of El Gergal were comparable to ebullitive fluxes found in temperate shallow ponds (Dove et al, 1999;DelSontro et al, 2016), a kind of ecosystem typically supporting higher CH 4 emission rates than temperate deep lakes and reservoirs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Global N 2 O fluxes from reservoirs was estimated at 31.7 Tg CO 2 eq./year (Deemer et al, 2016), which is notable, but a smaller contribution than CO 2 (328) and CH 4 (748) (Harrison et al, 2021). There was no clear trend in the spatial variation of N 2 O fluxes (Figure 3b; Table S6) with some studies reporting the highest average fluxes at the upstream river (Cheng et al, 2019), downstream river (Yang, 2019) and reservoir surface (Yang et al, 2020). Anoxic conditions in reservoir sediments can lead to conditions favourable for denitrification, generating N 2 O emissions (Wang et al, 2018).…”
Section: Greenhouse Gas Fluxes In Intermittent Riversmentioning
confidence: 96%
“…On average, CH 4 fluxes were an order of magnitude higher from the downstream reaches than from the reservoir surface and upstream reaches (Figure 3b). However, in individual studies the results were variable (Table S6), with observed CH 4 fluxes at the reservoir surface that were greater or lower than upstream (Yang, 2019; Yang et al, 2013) and downstream waters (Guérin et al, 2006; Zhao et al, 2013). Methane production may not translate directly to CH 4 efflux, as the upwardly diffusing CH 4 can be converted to CO 2 by methanotrophic bacteria (Wang et al, 2018).…”
Section: Greenhouse Gas Fluxes In Intermittent Riversmentioning
confidence: 99%